Statistical analysis of congenital anomlies in children in Lithuania - Marijus Radavičius; Jurgis Sušinskas; Algirdas Utkus (Lietuvos Matematikos Rinkinys)
Trends, prevalence and some influential (risk) factors of congenital anomlies in children in Lithuania are investigated using logistic regression model.